An open‐circuit fault diagnosis method for a submodule in a high‐frequency‐link modular multilevel DC transformer. Issue 1 (20th November 2020) - Zhang, Zhaoyun; Lin, Pu
Abstract: A high‐frequency‐link modular multilevel DC/DC transformer (H‐M2DCT) is used to interconnect DC bus bars of different voltage levels, and its safe and stable operation helps ensure the reliability of the entire DC grid. However, there is little research on the open‐circuit failures of H‐M2DCT submodules. Based on an electrical characteristics analysis of the open‐circuit fault of the H‐M2DCT submodule, this paper proposes a submodule open‐circuit fault detection method based on wavelet analysis. By performing wavelet analysis on each arm current, the coefficient is used as a criterion to detect whether a submodule open‐circuit fault has occurred on the arm; in terms of fault location, an over‐voltage protection method based on the submodule capacitor voltage is adopted. The proposed method requires neither the establishment of a complicated mathematical model nor the installation of additional sensors; thus, rapid detection and localisation of the fault submodule are achieved while reducing computational demand. In addition, the validity and effectiveness of the proposed method can be verified on the MATLAB/Simulink simulation platform.